Cities and metaphors beyond imaginaries of Islamic urban space - Falahat, Somaiyeh (Routledge research in planning and urban design, 2018)
In the context of Islamic city studies, relying on reasoning and rational thinking has reduced descriptive, vivid features of the urban space into a generic scientific framework. Phenomenological characteristics have consequently been ignored rather than integrated into theoretical components. The book argues that this results from a lack of appropriate conceptual vocabulary in our global body of scholarly literature. It challenges existing theories, introduces and applies the urban concept of Hezar-tu to rethink the spaces of Fez, Isfahan and Tunis. This tool inverts the principles of conceptualising urban space and constructs a staging-post towards a different articulation based on in-between spaces rather than nodes, a logic of ambiguity rather than determinacy, and interior rather than exterior thinking.?